Os fundos de investimento entre a regulação social do mercado e a proteção jurídica do investidor-consumidor - Alves, André Gomes de Sousa (2011)
This present dissertation is about the protection of small investors in mutual funds, through socio-economic regulation of the market, including by reason of failures related to asymmetric informations. For this, it was used dialectical approach method and comparative, historical, structural and functional methods of procedure, as well as the documentary and bibliographical techniques of research. Given today's economic and financial globalization, notably marked by increasing financing of economy and the consequent systemic capital, new challenges present to the legal complex and regulatory environment. Besides the active and coordinated brokering of new financial players, new institutional arrangements are also (re)created at the evolution of economic routine, denouncing the urgent need for a unique conformation of protective forces in the inclusive sense. In this context, representative of the current legal and contractual pluralization denoted from the collectivization of resources to further appreciation of the condominium property, while express the development of jusnaturalistic on a new order of the economy, mutual funds may also build in your negotiating arrangement market failures that tend to undermine the image of the small investor. Such as asymmetric informations, covert or incomplete on the contractual process, they are able to makes vulnerable the center of interest which applicate saved resources, creating an adversarial and hierarchical relationship between the latter (principal) and the agent. Thus, in response to this situation, the regulation of relationships between the mutual funds and small investor goes through before a concern with protecting the human figure, according the public interest to compensate possible deficits in social welfare. Relative truths such as the certainty and completeness of the law are then overtaken by the realization of microsystems and the legal and self-regulation of the market, promoting to the small investor the realization of fundamental rights, others resulting from its maximalist consideration as a consumer and others from enforcements of norms of conduct of financial market entities, such as the Comissão de Valores Mobiliários and the Associação Brasileira das Entidades dos Mercados Financeiro e de Capitais. Ultimately, advocates in defense of transparent information, honesty and loyalty contractual, and fair rights and obligations between the contractors, as a guarantee of the investor-consumer rights as well as regulatory protection.